2017
DOI: 10.18869/nrip.irj.14.4.217
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Faith in Work, Religious Beliefs, and Spirituality in the Prediction of Job Satisfaction Among Rehabilitation Experts

Abstract: Objectives: Integration of religion and spirituality in the workplace help people to be more satisfied with their job. The aim of the present study was to explore the role of religious beliefs, faith at work, and spirituality in the prediction of job satisfaction among rehabilitation experts. Methods:With the help of simple random sampling, 163 subjects (74 speech and language pathologists, and 89 occupational therapists) were selected from rehabilitation experts employed across educational clinics affiliated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It seems among Iranian students of nursing, some spiritual values are assimilated into job values and cause an increase in their satisfaction with clinical practice [46]. Although this finding was expected, it cannot be declared spirituality is always associated with positive outcomes in caregivers [47,48] and cannot necessarily predict their satisfaction [48].…”
Section: Discussionmentioning
confidence: 95%
“…It seems among Iranian students of nursing, some spiritual values are assimilated into job values and cause an increase in their satisfaction with clinical practice [46]. Although this finding was expected, it cannot be declared spirituality is always associated with positive outcomes in caregivers [47,48] and cannot necessarily predict their satisfaction [48].…”
Section: Discussionmentioning
confidence: 95%
“…Emmons (2000) used Gardner (1999) definition of intelligence as ''A set of abilities that are used to solve problems and create products that are valuable within a cultural setting or community'' to look at spirituality through the lens of intelligence (Emmons, 2000). The results of Rezapour, Rezai, Hosseini, and Mohseni Takalu's (2016) research showed that religious beliefs can have a significant role in the job satisfaction of rehabilitation staff. Bahrami, Farani, & Younesi's (2007) research suggested that external religious beliefs are related to mental health disorders, and Hamid and Dehghanizadeh (2012) showed that people with higher spiritual attention have better coping strategies in problemsolving and also have better mental health.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that among Iranian students of nursing, some spiritual values penetrate into job values and cause an increase in their satisfaction with clinical practice [48]. Although this nding was expected, it cannot be declared that spirituality is always associated with positive outcomes in caregivers [49,50] and cannot necessarily predict their satisfaction [50].…”
Section: Discussionmentioning
confidence: 99%